COMPARISON OF DRIP LOSS VALUES BETWEEN MUSCULUS INFRASPINATUS AND MUSCULUS GLUTEOBICEPS LOCAL CATTLE AFTER FROZEN-THAWING PROCESS - Fikar, Samsul; Razali, Razali; Sulasmi, Sulasmi (Universitas Djuanda Bogor, 2019)
Aimed this study to know about percentage of drip loss at Musculus infraspinatus and Musculus gluteobiceps local cows after freeze-thawing. Musculus infraspinatus and Musculus gluteobiceps is cutting about 50-75 gram for 15 sample. All sample is weighing for the first weigh and then freezing until 24 hours. After that thawing the sample until 24 hours too in refrigerator. Repeat this process until four season. The finally we can read drip loss in Musculus gluteobiceps is the bigger at process freeze-thawing fourth. Duncan test showing a diferent percentage of drip loss after freeze-thawing.Key words : Drip loss, freeze-thawing , Musculus infraspinatus and Musculus gluteobiceps